Fiber to The Home (FTTH) Network Design in Analyzing Macro Bending Problems in The Home Cable Installation Segment - Maria, Popi; Asri, Aprinal Adila; Yustini, Yustini; Wiharti, Wiwik; Prayama, Deddy (SOTVI, 2022)
Fiber to The Home (FTTH) is one of the optical networks used for every home in accessing the internet in the form of voice, data, and video. In this study, the authors built an FTTH design from a Handheld Light Source (HLS) as input, then connected it to ODC. Furthermore, it is connected with ODP, OTP, and ROSET. After building the design, the design was tested using the link power budget calculation method, which is 22.803 dB. As a result, the design has a total attenuation value of 18.4 dB which means it meets the standards and can be used. Next, analyze the problems that have the potential to cause macro bending interference in the FTTH home cable installation segment cable. The methods used in this macro bending problem are the HLS calibration method, Optical Power Meter (OPM) measurement, and Visual Fault Locator (VFL) macro damage detection. From this analysis, the results of macro bending will be obtained on the parameters of curvature diameter, the number of windings, and the search for critical angles of indoor cable macro bending. This macro bending in-home wiring installations affect the total attenuation value on FTTH. In addition, the macro bending of 3-winded indoor cables with a diameter of 0.5 cm on each winding still meets the standards in the FTTH design. However, for macro bending 5 windings with a diameter of 0.5 cm, each winding can cause the total attenuation value of FTTH to pass the Link power budget and ITU-T G984.